Environmentally Friendly Solvent‐Processed Organic Solar Cells that are Highly Efficient and Adaptable for the Blade‐Coating Method. Issue 4 (8th December 2017) - Zhao, Wenchao; Zhang, Shaoqing; Zhang, Yun; Li, Sunsun; Liu, Xiaoyu; He, Chang; Zheng, Zhong; Hou, Jianhui
Abstract: The power conversion efficiencies (PCEs) of state‐of‐the‐art organic solar cells (OSCs) have increased to over 13%. However, the most commonly used solvents for making the solutions of photoactive materials and the coating methods used in laboratories are not adaptable for future practical production. Therefore, taking a solution‐coating method with environmentally friendly processing solvents into consideration is critical for the practical utilization of OSC technology. In this study, a highly efficient PBTA‐TF:IT‐M‐based device processed with environmentally friendly solvents, tetrahydrofuran/isopropyl alcohol (THF/IPA) and o ‐xylene/1‐phenylnaphthalene, is fabricated; a high PCE of 13.1% can be achieved by adopting the spin‐coating method, which is the top result for OSCs. More importantly, a blade‐coated non‐fullerene OSC processed with THF/IPA is demonstrated for the first time to obtain a promising PCE of 11.7%; even for the THF/IPA‐processed large‐area device (1.0 cm 2 ) made by blade‐coating, a PCE of 10.6% can still be maintained. These results are critical for the large‐scale production of highly efficient OSCs in future studies. Abstract : Highly efficient non‐fullerene organic solar cells (OSCs) are fabricated, processed with environmentally friendly solvents, tetrahydrofuran/isopropyl alcohol (THF/IPA) and o ‐xylene/1‐phenylnaphthalene, respectively. The highest power conversion efficiency (PCE) of 13.1% can be achieved by adopting the spin‐coating method, which is the top result for OSCs. When the blade‐coating method is used in an ambient atmosphere, the THF/IPA‐processed device maintains a high PCE of 11.7%.